2001
DOI: 10.1046/j.1525-1497.2001.016007486.x
|View full text |Cite
|
Sign up to set email alerts
|

The challenge of problem residents

Abstract: Internal medicine residency training is demanding and residents can experience a wide variety of professional and personal difficulties. Residency programs everywhere have had and will continue to have problem residents. Training programs should be equipped to effectively identify and manage residents who experience problems. Previous articles that have been published on the topic of problem residents primarily addressed concerns such as impairment due to depression and substance abuse. The content of this art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
66
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 54 publications
0
66
0
Order By: Relevance
“…2 Some learners may not know how to navigate performance obstacles, making it important to offer guidance and oversight. 19,20 For this reason, we train a core group of faculty to help students apply the self-regulation cycle. 17 PAs coach students in reflection, self-assessment, and goal-setting.…”
Section: Discussionmentioning
confidence: 99%
“…2 Some learners may not know how to navigate performance obstacles, making it important to offer guidance and oversight. 19,20 For this reason, we train a core group of faculty to help students apply the self-regulation cycle. 17 PAs coach students in reflection, self-assessment, and goal-setting.…”
Section: Discussionmentioning
confidence: 99%
“…10 Programs for residents who need remediation have been described in published reports. [11][12][13] This approach, however, may neglect residents who are meeting or exceeding expectations, but may not reach their optimal potential. Research has shown that involving all residents in a structured program was useful in developing awareness of academic accomplishment, interpersonal communication skills, and professional behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…How big is the problem? The prevalence of residents requiring remediation varies by country, specialty and program, ranging from 5.8% to 9.1% (Yao & Wright 2001;Ratan et al 2008). There is scant literature focused on describing programs designed to improve resident performance (Ratan et al 2008).…”
Section: Introductionmentioning
confidence: 99%